(untitled) (مجلة إحالات, 2025)
يشكل موضوع الخطاب القصصي المرتكز السردي الذي يبنى عليه البناء القصصي حتّى وإن لمسنا تباينا في أساليب العرض والتشخيص، ولعل موضوع الخطاب التي أشرنا إليه آنفا يشكل لنا مظهرا من مظاهر الانسجام السردي الذي نلفيه في جميع متشابه القصص القرآني، وهذه الاستراتيجية التيمية تستند على المبدأ المركزي المنظم لمتتاليات الخطاب ، وأنّ لكل خطاب بنية كلية ترتبط بها أجزاء الخطاب وأن القارئ يصل إلى هذه البنية (الموضوع) عبر عمليات متنوعة تشترك كلها في سمة الاختزال وتشاكل المواقف والتكثيف السردي، ذلك أنّ القصة أو السورة مهما تعددت قضاياها، فهي كلام واحد يتعلق آخره بأوله، ويترامى بجملته إلى غرض واحد، كما تتعلق الجمل بعضها ببعض في القضية الواحدة. إنه لا غنى لمتفهم نظم السورة عن استيفاء النظر في جميعها كما لا غنى عن ذلك في أجزاء القضية. Abstract : The subject of the narrative discourse is the narratives based on narrative structures, even if we see a difference in the methods of presentation and diagnosis. Perhaps the subject of the discoures we mentioned above constitutes a manifestation of the narrative cohesion we achieve in all similar Qur’anic narratives. And the reader has access to this structure (subject) through various processes are all involved in the attribute of reduction and the change of attitudes and condensation narratives, because the story or the Sura no matter how many issues, it is one word related to another And in the whole sentence to the same purpose, as the sentences relate to each other in one case. It is indispensable for the understanding of the sura systems to complete consideration of all of them, as is indispensable in the parts of the case.